“Lo mejor de Chile está ahora en México”, ideas políticas y labor pedagógica de Gabriela Mistral en México (1922-1924) - Moraga Valle, Fabio (El Colegio de México, A.C., 2014)
This article looks at a brief and little-known period of the intellectual biography of the Chilean poet Gabriela Mistral (1889-1957), who was in Mexico from 1922 to 1924.  She arrived in Mexico to take part in Education Secretary Jose Vasconcelos’ project to implement cultural missions and rural education as primary axes of his post-revolutionary strategy to integrate country folk and indigenous peoples into the nation. This study focuses on two central areas of the poet’s life that have not been extensively researched, her political thought and her pedagogical ideas, both of which were formed not in formal education, but rather through her personal experiences and self-teaching. Contrary to traditional interpretations offered by biographers and literary experts, which suggest that Mistral fled under pressure from enemies and rivals and hating her native Chile, our hypothesis is that she chose to go to Mexico because it was the best place to carry out her pedagogical project and because she perceived there to be an atmosphere conducive to her political and intellectual aspirations.